Simple shelter device for indoor culture of procambarus clarkii - LI JIALE; QIAN ZHAOJUN; ZENG SHIMEI; JIANG HUCHENG (2015)
The utility model relates to a simple shelter device for indoor culture of procambarus clarkia. The simple shelter device comprises a shelter article and a bamboo pole, wherein the shelter article comprises a pipe, a gauze element and an iron wire, the pipe is in a semicircular shape, a side hole is formed in the side surface of the pipe, the periphery of the pipe is wrapped by the gauze element, the gauze element is fixed at the outer side of the pipe by virtue of the iron wire, the iron wire in the middle part of the pipe is provided with a first hook, and a second hook is arranged on the front end of the bamboo pole. The simple shelter device has advantages that the bottom, with the gauze element, of the device can be used for fixing waste in meshes formed by the gauze element, the waste can be prevented from being scattered when the procambarus clarkia moves and can be convenient to clear when the shelter device is moved; the shelter device is provided with the first hook, so that the shelter device is convenient to move, the body condition of the procambarus clarkia hidden in the shelter article can be periodically examined when the waste is cleared, the incubation of parent shrimps also can be observed, sick procambarus clarkia and dead procambarus clarkia can be removed in time, the spreading of the disease can be prevented, and the water quality can be prevented from going bad.